Peranan Satuan Polisi Pamong Praja Dalam Penertiban Pedagang Kaki Lima Di Pasar Pancur Batu Kecamatan Pancur Batu Kabupaten Deli Serdang - Silvia Tabhita Panggabean; Zulkarnain Lubis; Siti Mardiana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to analyze the role of the Civil Service Police Unit in controlling street vendors at Pancur Batu Market in Pancur Batu District, Deli Serdang Regency and the obstacles they faced. This study uses a descriptive method with qualitative analysis techniques which involve efforts such as asking questions and collecting specific data from participants, analyzing data. Results and discussion The role of Satpol PP in the norm has not been maximized because the street vendors operating at the Pancur Batu market only once a week. As an organization it has not been maximized because the number of personnel is still lacking and the transportation fleet is not sufficient. The social structure of the community is good because it has tried to create an orderly and comfortable community environment by adapting, discussing and socializing activities related to environmental order to the community and street vendors. The obstacle factor is institutional barriers, there are still many people in Pancur Batu Market who do not understand the importance of complying with various regulations, especially those relating to roadside use by street vendors. Barriers to human resources, namely the number of personnel is always not proportional to the tasks that must be done. Barriers to the network, namely the lack of cooperation with related agencies in the context of controlling street vendors at the Pancur Batu Market. Unfavorable environmental barriers. Obstacles to community participation, that is, the community lacks active participation